2015
DOI: 10.1002/pmic.201500159
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic network analysis in the sea urchin Strongylocentrotus purpuratus reveals new candidates in egg activation

Abstract: Fertilization triggers a dynamic symphony of molecular transformations induced by a rapid rise in intracellular calcium. Most prominent are surface alterations, metabolic activation, cytoskeletal reorganization, and cell-cycle reentry. While the activation process appears to be broadly evolutionarily conserved, and protein phosphorylation is known to play a key role, the signaling networks mediating the response to fertilization are not well described. To address this gap, we performed a time course phosphopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Consistent with this hypothesis, 174 conserved proteins alter their phosphorylation states during the egg-to-embryo transition in both sea urchin and the Drosophila (Krauchunas et al 2012, Guo et al 2015), suggesting that a cohort of phosphoregulated proteins is deeply conserved, and may be functionally important for the transition from oocyte to embryo.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…Consistent with this hypothesis, 174 conserved proteins alter their phosphorylation states during the egg-to-embryo transition in both sea urchin and the Drosophila (Krauchunas et al 2012, Guo et al 2015), suggesting that a cohort of phosphoregulated proteins is deeply conserved, and may be functionally important for the transition from oocyte to embryo.…”
mentioning
confidence: 72%
“…Guo et al (2015) observed 174 proteins in common between our dataset of proteins phospho-modulated during Drosophila egg activation (Krauchunas et al 2012) and their set of phosphoregulated proteins during this same transition in sea urchin. This led them to suggest that there are conserved cassettes of protein functions needed for this important developmental transition.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This fact implies that post-transcriptional modifications of Vasa are essential for its differential activities in each lineage and/or role. Vasa (DDX4) protein also appears phosphorylated in sea urchins (Guo et al, 2015), and potentially in mice and humans based on the search in the PhosphoSite proteomic database (http://www.phosphosite.org; Gustafson and Wessel, 2010), yet no detailed analysis has been provided especially in somatic cells. In the future, accomplishing the phosphor-proteomics analysis in the germ line, embryonic cells, regenerative tissues, and in tumor cells will likely reveal if Vasa undergoes differential modifications for each cellular process and for each development stage.…”
Section: Vasa Function Is Tightly Regulated By Post-transcriptional Mmentioning
confidence: 99%